2019
DOI: 10.1371/journal.pgen.1008011
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between mitochondria and diet mediates pathogen and stress resistance in Caenorhabditis elegans

Abstract: Diet is a crucial determinant of organismal biology; interactions between the host, its diet, and its microbiota are critical to determining the health of an organism. A variety of genetic and biochemical means were used to assay stress sensitivity in C. elegans reared on two standard laboratory diets: E. coli OP50, the most commonly used food for C. elegans, or E. coli HT115, which is typically used for RNAi-mediated gene knockdown. We demonstrated that the relatively subtle shift to a diet of E. coli HT115 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
92
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 86 publications
(116 reference statements)
9
92
1
4
Order By: Relevance
“…Old age metformin toxicity developed regardless of the bacterial viability and/or strain (Figure 1C and D) suggesting that late life metformin intolerance is independent of previously uncovered microbiome changes. Interestingly, the baseline survival of nematodes differed between UV killed OP50 and HT115 diets in line with recently reported dependence of nematode physiological behaviors on the bacterial source (Revtovich et al, 2019).…”
Section: Resultssupporting
confidence: 85%
“…Old age metformin toxicity developed regardless of the bacterial viability and/or strain (Figure 1C and D) suggesting that late life metformin intolerance is independent of previously uncovered microbiome changes. Interestingly, the baseline survival of nematodes differed between UV killed OP50 and HT115 diets in line with recently reported dependence of nematode physiological behaviors on the bacterial source (Revtovich et al, 2019).…”
Section: Resultssupporting
confidence: 85%
“…We found that wild type animals grown on E. coli OP50 had mildly increased mitochondrial fragmentation, which could be complemented by exogenous B12 supplementation ( Fig. 4B, lower panels), as has been observed (Revtovich et al, 2019). Moreover, Phsp-6::GFP was slightly induced on an E. coli OP50 diet, indicating mild mitochondrial dysfunction caused by B12 deficiency (Fig.…”
Section: Vitamin B12 Deficiency Increases Mitochondrial Fission and Msupporting
confidence: 80%
“…S13E). Mild B12 deficiency affected mitochondrial homeostasis and increased susceptibility to pathogenic infections in animals (46). However, in a drp-1/dynamin mutation background, B12 deficiency, on the contrary, improves C. elegans mitochondrial health by rebalancing mitochondrial fission-fusion events (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the C. elegans experiments differed in host (glp-4 vs glp-4; sek-1) and bacterial strains (S. aureus strain MRSA131 vs S. aureus strain MW2), timing, and even the host's diets varied (E. coli strain OP50 vs E. coli strain HB101). We have previously shown that switching the diet of C. elegans between the E. coli strains OP50 and HT115 significantly changes its susceptibility to P. aeruginosa PA14 [47], perhaps a similar phenomenon exists for S. aureus. Ultimately, much more work is needed to determine the potential of CD437 to treat S. aureus.…”
Section: Discussionmentioning
confidence: 88%